2012
DOI: 10.1007/s00401-012-1038-9
|View full text |Cite
|
Sign up to set email alerts
|

Electrophysiological changes precede morphological changes to frontal cortical pyramidal neurons in the rTg4510 mouse model of progressive tauopathy

Abstract: Whole-cell patch-clamp recordings and high resolution morphometry were used to assess functional and structural properties of layer 3 pyramidal neurons in early (< 4 months) and advanced (> 8 months) stages of tauopathy in frontal cortical slices prepared from rTg4510 tau mutant (P301L) mice. In early tauopathy, dendritic architecture is preserved. In advanced tauopathy, neurons can be categorized as either “atrophic” (58%)- exhibiting marked atrophy of the apical tuft, or “intact” (42%)- with normal apical tu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
135
6

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 124 publications
(156 citation statements)
references
References 58 publications
11
135
6
Order By: Relevance
“…Previous empirical and modeling studies have shown that dendritic morphology plays a critical role in determining passive membrane properties, including input resistance, and related neuronal firing rates (Mainen and Sejnowski, 1996;Euler and Denk, 2001;Vetter et al, 2001;Bekkers and Häusser, 2007;Weaver and Wearne, 2008;Amatrudo et al, 2012;Ferrante et al, 2013). Indeed, correlation analysis in our study suggests that there is a significant negative relationship between proximal (and total) apical dendritic branching com- plexity and input resistance in both Tbr2 and non-Tbr2 lineage neurons.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Previous empirical and modeling studies have shown that dendritic morphology plays a critical role in determining passive membrane properties, including input resistance, and related neuronal firing rates (Mainen and Sejnowski, 1996;Euler and Denk, 2001;Vetter et al, 2001;Bekkers and Häusser, 2007;Weaver and Wearne, 2008;Amatrudo et al, 2012;Ferrante et al, 2013). Indeed, correlation analysis in our study suggests that there is a significant negative relationship between proximal (and total) apical dendritic branching com- plexity and input resistance in both Tbr2 and non-Tbr2 lineage neurons.…”
Section: Discussionmentioning
confidence: 99%
“…A series of hyperpolarizing and depolarizing current steps (200 ms or 2 s in duration) were applied to each cell to assess passive membrane, single action potential, and repetitive action potential firing rates as described previously (Rocher et al, 2010;Crimins et al, 2012). Thirty electrophysiological variables were assessed in this study and quantified as follows.…”
Section: Electrophysiologymentioning
confidence: 99%
See 2 more Smart Citations
“…The assumption that mislocalization of tau into the somatodendritic compartment (6) and accumulation of fibrillar aggregates in NFTs mediates neurodegeneration underlies most current therapeutic strategies aimed at preventing NFT formation or disrupting existing NFTs (7,8). Although several disease-associated mutations cause both aggregation of tau and neurodegeneration, whether NFTs per se contribute to neuronal and network dysfunction in vivo is unknown (9). Here we used awake in vivo two-photon calcium imaging to monitor neuronal function in adult rTg4510 mice that overexpress a human mutant form of tau (P301L) and develop cortical NFTs by the age of 7-8 mo (10).…”
mentioning
confidence: 99%